Analysis of The Influence of Strategic Leadership in Increasing Financial Performance - Puspita Putri Kirana (Journal of Management and Business Environment (JMBE), 2019)
This research was to analyze the influence of strategic leadership in increasing financial performance in CV SB, an entertainment company in Semarang. Here, strategic leadership was measured using four indicators as in Lumpkin and Dess (1996), namely promotion, mentoring, discipline, and cooperation. This research used qualitative descriptive to describe and picturize situations of the object based on facts. Observation on operations of the company, interview to the manager and several employees, as well as documentation were to collect data. Triangulation was to validate the data in which data reduction, data presentation, and conclusion were the process in analysis. The result shows that the four indicators of leadership have run well and they influenced the promotion and human resource programs of the company that in turn positively affect financial performance. More specifically, promotion and mentoring influenced promotion program, while discipline and cooperation influenced human resource program.